Effect of vitamin E (Tri E®) on antioxidant enzymes and DNA damage in rats following eight weeks exercise - Mazlan Musalmah; Baruah Prasamit S; Ibrahim Ibrahim A; Ruzanna Rusdiah J; Hasrul Mohd A; Abd Hamid Noor Aini; Mohd Yusof Yasmin Anum; Wan Ngah Wan Zurinah (Nutrition Journal, 2011)
Abstract Background Exercise is beneficial to health, but during exercise the body generates reactive oxygen species (ROS) which are known to result in oxidative stress. The present study analysed the effects of vitamin E (Tri E®) on antioxidant enzymes; superoxide dismutase (SOD), glutathione peroxidase (GPx), catalase (Cat) activity and DNA damage in rats undergoing eight weeks exercise. Methods Twenty four Sprague-Dawley rats (weighing 320-370 gm) were divided into four groups; a control group of sedentary rats which were given a normal diet, second group of sedentary rats with oral supplementation of 30 mg/kg/d of Tri E®, third group comprised of exercised rats on a normal diet, and the fourth group of exercised rats with oral supplementation of 30 mg/kg/d of Tri E®. The exercising rats were trained on a treadmill for 30 minutes per day for 8 weeks. Blood samples were taken before and after 8 weeks of the study to determine SOD, GPx, Cat activities and DNA damage. Results SOD activity decreased significantly in all the groups compared to baseline, however both exercised groups showed significant reduction in SOD activity as compared to the sedentary groups. Sedentary control groups showed significantly higher GPx and Cat activity compared to baseline and exercised groups. The supplemented groups, both exercised and non exercised groups, showed significant decrease in Cat activity as compared to their control groups with normal diet. DNA damage was significantly higher in exercising rats as compared to sedentary control. However in exercising groups, the DNA damage in supplemented group is significantly lower as compared to the non-supplemented group. Conclusions In conclusion, antioxidant enzymes activity were generally reduced in rats supplemented with Tri E® probably due to its synergistic anti-oxidative defence, as evidenced by the decrease in DNA damage in Tri E® supplemented exercise group.